Decontamination of ubiquitous harmful microbial lineages in water using an innovative Zn2Ti0.8Fe0.2O4 nanostructure: dielectric and terahertz properties - Amany Mohamed El Nahrawy; Ali Belal Abou Hammad; Ahmed Mohamed Bakr; Bahaa Ahmed Hemdan; Ahmed Ramzy Wassel (Heliyon, 2019)
Many ubiquitous dangerous microbial lines could originate in different sources of polluted water and be distributed to tap water, which could cause multiple types of illnesses to humans and livestock. Despite enormous attempts to guarantee safety of potable water, these species are still regarded to be threated prevalent health issues and concerns. However, these species need a powerful disinfectant to be removed from contaminated water for receiving clean and healthy water. This study was therefore conducted to produce magnificent magnetic iron titanate zinc nano-particles (Zn2Ti0.8Fe0.2O4 MNPs) as a sophisticated approach for drinking water (DW) and wastewater purification. The identification of crystalline phase, dielectric and terahertz spectroscopy of iron zinc titanate nanostructure prepared via acidic sol-gel process and calcined at 800 °C. Results show that the formation of cubic structure for Zn2TiO4 phase, and the dielectric constant (εʹ) decreased with the higher frequency, tan (δ) has higher values at lower frequency and the conductivity increases relatively with frequency that attributes to the high resistive grain boundaries. Absorption coefficient, refractive index and dielectric properties of iron zinc titanate nano-particles was estimated via time domain-terahertz spectrometer and adjusted via the applied electric field. In particular, the Gram-negative bacteria were more prone than other microbes tested to the Magnetic Nano-Particles (MNPs). Results also was ascertained that the minimum inhibitory concentration (MIC) was 25 ppm at 30 min for E. coli and Salmonella enterica, 45 min for Listeria monocyteogens, Staphylococcus aureus, and Candida albicans and 60 min for Aspergillus niger with a noticeable bactericidal impact. Results exhibit that the MNPs explored are non-toxic and protected for individuals and the environment. MNPs can, therefore, be proposed as an expedient and impressive nano-scale applicant for inactivation during the drinking water and wastewater conservation of the prevailing dangerous microbes.